KESEHATAN SEKSUAL ISTRI DENGAN PENGALAMAN KEKERASAN SEKSUAL SEBELUM MENIKAH - Nuristighfari Masri Khaerani (Jurnal Psikologi Integratif, 2013)
Sexual health is a state of physical, emotional, mental, and social well-being in relation to sexuality; it is not merely the absence of disease, dysfunction, or infrmity. Sexual health requires a positive and respectful approach to sexuality and sexual relationships, as well as the possibility of having pleasurable and safe sexual experiences, free of coercion, discrimination, and violence. For sexual health to be attained and maintained, the sexual rights of all persons must be respected, protected, and fulflled. The aim of this study was to describe sexual health among wife who experience sexual violence before marriage. Respondents of this research are three wifes who experience sexual violence before marriage. Result of this research show that all participants were not satisfed with their sexual life. Other fndings of this research show that the experience of sexual violence create social disfunction, interpersonal diffculties, lower quality of romantic relationship, revictimization of sexual violence, earlier sexual debut, and neglect their own children.